2019
DOI: 10.2147/cia.s164021
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship between abnormal glucose metabolism and osteoporosis in Han Chinese men over the age of 50 years</p>

Abstract: Aim The aim of this study was to determine the relationship between abnormal glucose metabolism and osteoporosis (OP) in Han Chinese men over the age of 50 years. Patients and methods A cross-sectional study of 775 male patients aged over 50 years was performed at our hospital in 2011. The patients were divided into a normal glucose metabolism group, an impaired glucose regulation (IGR) group, and a type 2 diabetes mellitus (T2DM) group. Differences in their bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…BMD is measured to assess osteoporosis in many medical institutions. Although previous studies have reported that the BMD of patients with T2DM was normal or even higher than that of nondiabetic controls, the fracture risk was higher in patients with T2DM [4,26]. Our study also showed that the BMD levels between T2DM and non-T2DM patients were similar (p = 0:131), although the T2DM population had a higher risk for fractures (OR 1.357).…”
Section: Discussioncontrasting
confidence: 48%
“…BMD is measured to assess osteoporosis in many medical institutions. Although previous studies have reported that the BMD of patients with T2DM was normal or even higher than that of nondiabetic controls, the fracture risk was higher in patients with T2DM [4,26]. Our study also showed that the BMD levels between T2DM and non-T2DM patients were similar (p = 0:131), although the T2DM population had a higher risk for fractures (OR 1.357).…”
Section: Discussioncontrasting
confidence: 48%
“…6 However, there was a study showed the detection rates of low BMD and osteoporosis have no significant differences among different glucose metabolism groups. 7 Meta-analysis results also indicated that abnormal glucose metabolism showed no significant correlation with BMD or bone metabolism. 8 The effect of obesity on BMD is associated with varied factors, but the relationship between obesity and osteoporosis still remains to be controversial, 9 and it is inconclusive whether obesity increases or decreases BMD.…”
Section: Introductionmentioning
confidence: 99%
“…The ovarian function and estrogen level continuously decline in women relative to age, ultimately leading to osteoporosis (OP) ( 1 ). OP is one of the common complications of patients with type 2 diabetes mellitus (T2DM), causing great morbidity and seriously affecting the quality of life of patients ( 2-4 ). Currently, the main therapeutic methods for elderly patients with T2DM and OP include calcium and vitamin D supplements, physical exercise, specified diet and high quality nursing, yet the occurrence and progression of OP in elderly patients with T2DM cannot be effectively controlled ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%